Canal irrigation conundrum: applying contingency theory to irrigation system management in India. - Shah, Tushaar; Anwar, Arif A.; Amarasinghe, Upali A.; Hoanh, Chu Thai; Reddy, Junna Mohan; Molle, Francois; MMukherji, Aditi; Prathapar, Sanmugam A.; Suhardiman, Diana; Qureshi, Asad Sarwar; Wegerich, Kai (International Water Management Institute, 2012)
This report presents a discussion among IWMI?s Asian researchers on the strategy for policy research on canal irrigation in India. Poor service delivery, persistence of head-tail inequity, growing gap between irrigation potential created and utilized, shrinking of command area despite growing investments in construction and rehabilitation, sustained build up of deferred maintenance of infrastructure, patchy performance of Farmer Participatory Irrigation Management, poor service fee recovery - these are part of the litany of problems that concern irrigation managers and policy makers in India and elsewhere in Asia. This paper argues that state, society, technology and agrarian institutions - all had a better ?fit? with the canal irrigation technology during the colonial and earlier times in ways that does not obtain today. A contingency hypothesis is proposed to explore why, as socio-technical systems, canal irrigation systems would behave differently under different ?contingency clusters?. A research program around irrigation management performance benchmarking - with four meta questions - was proposed but received little support from the IWMI research group. The paper concludes the discussion with the lead author?s dissenting note which argues that, though difficult, benchmarking of managerial performance - as routinely done in businesses, educational institutions, governments, even research institutions - may be the way to go if IWMI aims to contribute to effective reform in canal irrigation management.